Threating messages, risk perception and the intent of smoking cessation. The case of stundent smokers at Athens Panteion University - Simoudi, Christina; Alexias, George; Tsekeris, Charalambos (Italian Sociological Review, 2014)
A plethora of campaigns focuses on communicative practices, such as the use of public warnings in the form of advertisements, with the aim of informing smokers about the potential risks of starting and maintaining smoking. Conducted researches have shown the effectiveness of such campaigns on smoking cessation. The present survey examines the influence of threatening messages given to 150 smokers, who are students of Athens Panteion University, aged between 18 and 28, by estimating subjective risk perception, the intention to quit smoking within 30 days and within 6 months, and the disengagement beliefs. The participants were separated in two groups, the control group and the experimental group, in which they received a threatening message, and subsequently completed the questionnaire. The results indicated that smokers in the experimental group had higher subjective risk perception. In specific, those who were in the later stages of changing behaviour appeared to have a higher intention to quit smoking. The smokers’ high adherence to disengagement beliefs reduced the risk perception, but there is a correlation between disengagement beliefs and groups related to this variable. The results suggest that threatening messages are an effective strategy for preventing and motivating people to quit smoking.